The Strategy Planning Process Analyses, Options, Projects - Grünig, Rudolf (Springer Berlin Heidelberg, 2018)
Developing future strategies for a company is an important and complex task, and forms the core issue in this book. A company's strategy defines its future direction, specifying its desired market position and key competitive advantages both at the level of market offers and of resources. This book provides clear, straightforward advice for professionals: after a brief introduction to strategic planning, a heuristic process for determining future strategies is presented. It shows how to analyze a company's current situation, develop and assess options for the future, and define implementation projects. Throughout the book, detailed recommendations are illustrated with the help of numerous concrete examples. As a result of studying applications of the book in practice, the second edition benefits from a simplified, hands-on analysis and planning process at the business level.